2001
DOI: 10.1016/s1534-5807(01)00005-3
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Glypican Knypek Controls Cell Polarity during Gastrulation Movements of Convergent Extension

Abstract: Mutations in the zebrafish knypek locus impair gastrulation movements of convergent extension that narrow embryonic body and elongate it from head to tail. We demonstrate that knypek regulates cellular movements but not cell fate specification. Convergent extension movement defects in knypek are associated with abnormal cell polarity, as mutant cells fail to elongate and align medio-laterally. Positional cloning reveals that knypek encodes a member of the glypican family of heparan sulfate proteoglycans. Doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
511
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 420 publications
(551 citation statements)
references
References 58 publications
35
511
2
3
Order By: Relevance
“…Under conditions of brief exposure to chemoattractant, cells can respond quickly to turn in any direction (Soll et al, 2002). As has been seen in other teleosts (Trinkaus et al, 1992;Trinkaus, 1998), we find greater meandering in ventral versus lateral mesoderm, which is further from the hypothesized source of dorsal attractant (Myers et al, 2001;Topczewski et al, 2001;Jessen et al, 2002). In contrast, while moving up a gradient of chemoattractant, Dictyostelium form few lateral processes and show reduced turning (VarnumFinney et al, 1987).…”
Section: Comparing Migration Of Lateral Mesoderm To Chemotaxissupporting
confidence: 82%
See 4 more Smart Citations
“…Under conditions of brief exposure to chemoattractant, cells can respond quickly to turn in any direction (Soll et al, 2002). As has been seen in other teleosts (Trinkaus et al, 1992;Trinkaus, 1998), we find greater meandering in ventral versus lateral mesoderm, which is further from the hypothesized source of dorsal attractant (Myers et al, 2001;Topczewski et al, 2001;Jessen et al, 2002). In contrast, while moving up a gradient of chemoattractant, Dictyostelium form few lateral processes and show reduced turning (VarnumFinney et al, 1987).…”
Section: Comparing Migration Of Lateral Mesoderm To Chemotaxissupporting
confidence: 82%
“…We previously observed that lateral mesodermal cells (80% epiboly, 8.4 hpf) migrated primarily dorsally, frequently with substantial animal or vegetal bias and showed quite variable net dorsal speed (Jessen et al, 2002). Finally, our previous studies in which lateral mesodermal cells labeled at early gastrulation were visualized at early segmentation stages provided another hint of difference in path orientation along the AnVg axis of the mesoderm (Sepich et al, 2000;Topczewski et al, 2001). The labeled cell group moved toward the dorsal midline, forming a broken line along the animal-vegetal (or anterior-posterior) axis.…”
Section: Movement Behaviors Of Lateral Mesodermal Cells Vary Along Thmentioning
confidence: 81%
See 3 more Smart Citations